Evaluating conditional asset pricing models for the German stock market - Andreas Schrimpf; Michael Schröder; Richard Stehle (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
We study the performance of conditional asset pricing models in explaining the German cross-section of stock returns. Our test assets are portfolios sorted by size and book-to-market as in the paper by Fama and French (1993). Our results show that the empirical performance of the Capital Asset Pricing Model (CAPM) can be improved substantially when allowing for time-varying parameters of the stochastic discount factor. A conditional CAPM with the term spread as a conditioning variable is able to explain the cross-section of German stock returns about as well as the Fama-French model. Structural break tests do not indicate parameter instability of the model - whereas the reverse is found for the Fama-French model. Unconditional model specifications however do a better job than conditional ones at capturing time-series predictability of the test portfolio returns.
Keywords: G12; 330; Asset Pricing; Conditioning Information; Hansen-Jagannathan Distance; Multifactor Models